Metabolic flux balance analysis of the growth of arabidopsis thaliana cell suspension cultures - Mohamad Puad, Noor Illi (2015)
A stoichiometric model was developed for the application of metabolic flux balance analysis (FBA) which consisted of the primary metabolic network of Arabidopsis thaliana (A. thaliana). The basic metabolic model involved 149 metabolites and 178 reactions that represent the main carbon metabolism towards the formation of biomass. Assuming pseudo-steady state, mass balances were performed for each metabolite and the resulting equations were solved using linear optimization. The optimal metabolic flux distribution was determined in General Algebraic Modeling System (GAMS) 23.0 software by setting up the objective function as the maximization of biomass formation rate and using the constraints from batch experiments of A. thaliana suspended cell cultures. The results gave the theoretical maximum biological capacity of the cells to grow for a given specific uptake rate of sugar. The model proved to be a good starting point for more extended version of metabolism specifically for secondary metabolite production. Addition or extension of the model is feasible.